PENGARUH PENYELENGGARAAN FULL DAY SCHOOL TERHADAP MOTIVASI BELAJARKELAS X SMKN 5 PONTIANAK - Dian Hayati; Achmadi Achmadi; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study entitled the effect of full day school implementation on learning motivation of class X AK students at SMK Negeri 5 Pontianak and aims to determine whether there is an influence and how much full day school implementation on learning motivation of class X AK students at SMK Negeri 5 Pontianak. The research method used is a descriptive method with the form of research using interrelationship studies. In this study, the population data source is all students of class X AK,amounting to 37 people. The results of data analysis in this study indicate a simple regression equation Y '= 6.881 + 1.385x which means that if the implementation of full day school is 0 (zero), then the motivation to learn is positive, namely 6.881 and each decrease in the implementation of full day school is worth 1 (one). Then the motivation to learn will also decrease by 1.385. The result of the determination coefficient is 0.546 which means that the implementation of full day school has an effect of 54.6% on the learning motivation of class X AK students of SMK Negeri 5 Pontianak and is included in the moderate influence category. Keywords: Full Day School Implementation, Learning Motivation.